Education and Labour - Lempertas, Izraelis (Problemos, 1968)
The paper gives some results of the tests that were carried out at the “Audėjas” textile factory and the central enterprise of the sewing factory “Lelija” by the sociological research laboratory of the Vilnius V. Kapsukas State University in 1965-1966. 376 workers, selected accordingly to the accidental 12% selection, were interviewed. The paper analyses the influence of education upon certain indexes defining the basic parameters of the workers’ industrial activity (fulfilment of production quotas, quality of production, initiative, discipline) in accordance with the contents of their work. The analysis is carried out by calculating the coefficients of twin correlation. The influence of education, qualification and industrial experience upon these indexes is compared and the correlation between the education and qualification of the workers is investigated. On the basis of the data obtained, recommendations aimed at increasing the workers’ personal interest to raise their qualifications are given and some problems associated with the implementation of general secondary education, which are outlined in the five year plan, are considered.